Use of Antifungals and Outcomes Among Inpatients at Risk of Invasive Aspergillosis or Mucormycosis in the USA: A Retrospective Cohort Study - Katherine Stull; Elizabeth Esterberg; Mayank Ajmera; Sean Candrilli; Therese M. Kitt; James R. Spalding; Vanessa Perez Patel (Infectious Diseases and Therapy, 2019)
Abstract Introduction Prophylaxis and treatment of invasive aspergillosis (IA) and mucormycosis (IM) within a real-world US inpatient setting is undocumented since the introduction of isavuconazole. This retrospective medical record review aimed to describe characteristics, triazole use, and outcomes among inpatients across the USA who initiated antifungal monotherapy (AFMT) as prophylaxis or treatment of IA/IM. Methods A convenience sample of US physicians abstracted data from randomly selected records of hospitalized patients aged ≥ 18 years initiating AFMT (amphotericin B, isavuconazole, voriconazole, or posaconazole) as prophylaxis or treatment of IA/IM between 2013 and 2017. Retrieved data included background characteristics, dosage and duration of AFMT, healthcare resource use, and survival. Characteristics and outcomes were compared (prophylaxis vs treatment) using Fisher’s exact and one-way analysis of variance tests where applicable. Exploratory Kaplan–Meier analyses described overall and inpatient survival. Results Physicians (n = 23) retrieved 124 patient records (43 prophylaxis; 81 treatment). Median duration of first-line AFMT was 14 days (range 1–603 days) and 19 days (range 3–351 days) in the prophylaxis and treatment groups, respectively. One patient received second-line therapy. Median duration of hospitalization was 29 days (range 4–259 days) and 31 days (range 6–980 days) in the prophylaxis and treatment groups, respectively. Admission to intensive care occurred in 14% and 52% of patients in the prophylaxis and treatment groups, respectively. At the time of data retrieval, overall and inpatient survival rates in the prophylaxis group were 88% and 87%, respectively, and in the treatment group were 66% and 76%, respectively. Conclusions This study documented real-world prophylactic and therapeutic AFMT use for IA/IM and associated outcomes among hospitalized patients in the USA since approval of isavuconazole. IA/IM were associated with lengthy hospital stays commonly requiring intensive care. Prophylactic and therapeutic AFMT dosages and duration generally followed recommendations and switching between agents was rare. Funding Astellas Pharma Global Development, Inc., Northbrook, IL, USA.